Territorializations of the “reisado” joking in Caraúbas community (Graça, Ceará) - Moraes, Antonio Jarbas Barros de (Geosaberes; Vol 9 No 19 (2018): Sept - Dec, 2018)
This research aims to show an approach based on the research experiences that took place in “Festa de Reis” (translated as “Festival of Kings”) of the community of Caraúbas, in Graça / CE in 2016 and 2017. Therefore, we selected one of the sections of the master’s degree dissertation, specifically, on the territorialization of the party . We interpreted experiences through fieldwork that consisted of follow-up, interviews and filming of the groups of “reisados”. We anticipate that the festival of kings develops multiple relationships and movements created by the people who transform and characterize the mobile territory. From this assumption we show that the interlocutors trigger diverse tactics for the composition of the territory that permeate economic, political, moral and cultural relations that deserve to be discussed in the Geography.